Using Presence Circles to identify strategies to enhance nurse presence at discharge: a focus group study with nursing students - Marie C. Haverfield; Sara Nayeem; Meaghan Sterk; Stacy Demertzis; Deborah Szeto; Robin Whitney (International Journal of Nursing Studies Advances)
Background: Nurse communication of patient needs at discharge is critical to ongoing care, but system-level demands often prohibit comprehensive discharge conversations. Caregivers of discharged patients frequently report feeling underprepared to meet patient needs. Meaningful interpersonal encounters, or presence, are known to enhance clinical interactions amidst system-level demands, which could help improve caregiver preparedness and patient care. Purpose: To explore and synthesize examples of nurse presence during discharge conversations through Presence Circles (structured focus groups) to provide recommendations for enhancing high-quality information at discharge. Methods: In a secondary analysis of data from a larger study based on the Nurse Presence Framework, nursing students (N = 14) from a Northern California school were asked to participate in two Nurse Presence Circles. Audio recordings from 10 Presence Circles were transcribed and analysis was conducted according to the five practices of the Nurse Presence framework: Prepare with Intention, Listen Intently and Completely, Agree on What Matters Most, Connect with the Story, and Evolve System-Level Change. Results: Within each of the five nurse presence practices, strategies and challenges were collapsed into broader themes that served as recommendations for enhancing the exchange of high-quality information at discharge. Conclusions: Presence Circles offered a useful space to share strategies and identify system changes that could advance the exchange of high-quality information at discharge. We have provided a synthesis of recommendations for nurses, particularly those new to discharge conversations or early in their nursing career, demonstrating the need to engage nursing students about discharge conversations and introduce considerations related to health care systems and policy to better support the discharge conversation experience.